Die Rolle der Querflöte im Musikleben der Griechen und Römer: Elmar Bringezu zum 50. Geburtstag - Scheithauer, Andrea (International journal of musicology, 1996)
This is a study in the origin and use of the plagiaulos. It gives a new assessment of the role of this instrument in ancient society and of the social status of its players. In an appendix, relevant evidence, both numismatic and archaelogical, is collected.